Development of Ceker Media and Space Building for Light Mild Mental Retardation Students of SMPLB Pekanbaru - Heleni, Susda; Zulkarnain, Zulkarnain; Afriliziana, Linda Ardani (Journal of Educational Sciences, 2021)
In conveying the concept of mathematics in a concrete manner so that it is easily accepted by participants in the mentally retarded education, tools/media are needed. One of the media developed in this study for mentally retarded students is Ceker media and space building media. This study aims to produce Ceker learning media on number material and spatial shapes on blocks and cubes for mild mental retardation students at SMPLB Pekanbaru that meet valid and practical criteria. The research method used is the Borg and Gall development model. Collecting validation data for the addition and subtraction of integer operation materials was carried out by providing validation sheets to three experts. Practical data collection was carried out by distributing questionnaires to SMPLB mental retardation students using a Likert scale . The learning media of Ceker and building spaces that have been validated by 3 validators are very valid with a percentage of 93,3. The development of learning media for Ceker cards and building space for mild mentally retarded students has met the very practical criteria with a percentage of 100%. Based on the results of the research and discussion, it was concluded that the learning media of Ceker and building spaces (blocks and cubes) for mild mental retardation students at SMPLB have met the criteria of being very valid and very practical.